Real exchange rate and manufacturing growth in Latin America - Paulo Henrique Vaz; Werner Baer (Latin American Economic Review, 2014)
The manufacturing sectors in Latin America have been more affected by the currency over/undervaluation than their counterpart in industrialized economies. From a panel data set covering 39 countries and 22 manufacturing sectors (2-digit) within 1995-2008, we formally test the hypothesis that there exists a Latin American effect and then investigate the possible reasons for this distinguished pattern. The use of a disaggregated data is an important feature of our empirical strategy: the undervaluation index (main covariate) is less likely to be determined by the growth rate of a specific manufacturing sector, partially addressing the specification problem that plagues standard cross-country regressions. We then explore the within sector-country variation to study the relationship between currency over/undervaluation and manufacturing sectors growth. We find that the import content of exports might be an important driver of this result at a sectoral level. At a macro-level, the openness and the income per capita of a country are important factors.
Keywords: O23; O24; O25; 330; Real currency appreciation; De-industrialization; Manufacturing growth; Latin America